INDIVIDUAL COUNSELING UTILIZING STABILIZATION TECHNIQUE FOR HELPING JUNIOR STUDENTS WHO WERE CYBERBULLIED - Mianklang, Arjaree; Kaewchinda, Marid (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
The purpose of this study was to examine 1) the situation of being Cyberbullied 2) Individual counseling using Stabilization techniques for students who were Cyberbullied. The qualitative research methodology was used. The participants were 499 junior school students in the academic year 2017, filled in the questionnaire for this study. Two students who experienced cyberbullied participated in 4 individual counseling sessions with stabilization techniques (Inner Safe Place, Inner Container, Light Stream Technique). The descriptive statistics (26.10) were utilized the data analysis. The results revealed that 1) One-hundred and thirty (26.10) of participants had experiences of Cyberbullied. Among 499 participants, one-hundred and one participant (20.20) received the rude message and threatened messages, which is the highest number among several types of Cyberbully. The impacts of Cyberbully affected in many areas, stress issues (16.80), nervous (14.00), and anxiety (13.20). In short, individual counseling with stabilization techniques could support students to enhance their coping skills toward being Cyberbullied properly.